Polymetallic mining tailings reuse within the framework of circular economy for concrete production - Ojeda Zamudio, Andrea Carolina (2024)
Mining is one of the economic sectors that generates the greatest wealth in Peru, however, the tailings produced by it can negatively impact the environment, if they are not properly treated, and their storage also implies high costs for the mining industries. To find a solution within the framework of the circular economy, this work seeks to determine the technological and environmental feasibility of replacing traditional concrete sand with polymetallic tailings. Therefore, different mixtures of concrete with polymetallic tailings were made to determine the workability, unit weight, temperature, air content, and resistance of each of them. Consequently, it was concluded that polymetallic tailings can partially replace sand in conventional concrete for basic structural applications such as floors, walls, and pedestals.